Analisis Efisiensi Saluran Pemasaran Manisan Carica Di CV Gemilang Kencana Desa Siyono Bojosari Kecamatan Kretek Kabupaten Wonosobo - Niswah, Izzatun; Prabowo, Rossi; Wahyuningsih, Sri (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Carica candy is a processed horticultural product typical of Wonosobo Regency that has relatively high economic value. The success of carica candy marketing is strongly influenced by the efficiency of the marketing channels used. This study aims to analyze marketing channels, marketing margins, farmer’s share, and the efficiency level of carica candy marketing channels at CV Gemilang Kencana, Siyono Bojasari Village, Kretek District, Wonosobo Regency. This research employed a quantitative descriptive method. Data were collected through interviews, observations, and documentation involving producers and marketing institutions participating in the distribution of carica candy. Data analysis included marketing channel analysis, marketing cost and margin analysis, farmer’s share analysis, and marketing efficiency analysis. The results showed that there are four marketing channels for carica candy: (1) producer–agent–consumer, (2) producer–agent–retailer–final consumer, (3) producer–agent–wholesaler–final consumer, and (4) producer–agent–wholesaler–retailer–final consumer. The farmer’s share value in all marketing channels exceeded 50 percent, with the highest value found in marketing channel I and the lowest in marketing channel IV. Marketing efficiency values for carica candy with 4-pack ranged from 4.3% to 6.6%, 6-pack ranged from 2.4% to 4.6%, and 12-pack ranged from 1.4% to 2.4%. All marketing channels were categorized as efficient because their efficiency values were below 50 percent. Marketing channel I was identified as the most efficient channel.